Analisis dan Upaya Pengurangan Logam Berat Pb Pada Air Dalam Pengolahan Tahu Dengan Arang Aktif Tempurung Kelapa Menggunakan Spektrofotometri Serapan Atom - Saidah, Saidah; Supriyadi, Supriyadi; Harmastut, Nuraini (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Lead (Pb) is a toxic heavy metal that can contaminate water, including wastewater from tofu processing. Untreated sewage may adversely affect the environment and human health. One effective method for Pb reduction is adsorption using activated coconut shell charcoal, which possesses high porosity and surface area. Objective: This study aimed to analyze the adsorption efficiency of Pb in tofu wastewater using activated coconut shell charcoal and determine the optimal adsorption conditions based on adsorbent dosage, contact time, and pH. Methods: Water samples were collected from a tofu factory in Banjarsari, Solo. Coconut shell charcoal was activated with NaOH and used as an adsorbent. Optimization was performed by varying the adsorbent dosage (6, 8, 10 g), contact time (30, 60, 90 minutes), and pH (6, 7, 8). Lead (Pb) levels were quantified using Atomic Absorption Spectrophotometry (AAS). Results: The highest adsorption efficiency was 85.54% under optimal conditions: 8 g adsorbent dosage, 90 minutes contact time, and pH 8. Statistical analysis using ANOVA confirmed that all three factors significantly influenced Pb adsorption. Conclusion: Activated coconut shell charcoal effectively reduces Pb levels in tofu wastewater. Prolonged contact time, moderate adsorbent dosage, and alkaline pH enhance adsorption efficiency. This study proposes an environmentally friendly solution for treating wastewater from the tofu industry.